2018
DOI: 10.1111/jcal.12314
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the adoption of MOOCs: A technology–user–environment perspective

Abstract: In spite of the potentials promised by MOOCs (massive open online courses), the adoption rate of MOOCs is still low, especially in developing countries. Research on the adoption of MOOCs in developing countries is also limited. To fill this research gap, this research aims to study the adoption of MOOCs by extending current research on innovation and technology adoption in order to promote the diffusion of MOOCs in developing countries. Here, a conceptual framework, technology–user–environment was proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 35 publications
6
85
2
3
Order By: Relevance
“…Based on the perceptions of Chinese learners, their results indicated that fulfillment of basic psychological needs namely, relatedness, competence and autonomy, develop intrinsic motivation in learners which in turn increases their psychological engagement in MOOCs. Recently Ma and Lee (2019) presented a model based on technology-user-environment (TUE) framework to investigate the Chinese learners' adoption behavior of MOOCs. They considered perceived usefulness, performance-to-cost value, interactivity, and accessibility under the technology factors; self regulation, experience, and gender, under the user factors; and learning tradition, peers' impact, instruction and publicity, as the social environmental factors within the TUE framework.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the perceptions of Chinese learners, their results indicated that fulfillment of basic psychological needs namely, relatedness, competence and autonomy, develop intrinsic motivation in learners which in turn increases their psychological engagement in MOOCs. Recently Ma and Lee (2019) presented a model based on technology-user-environment (TUE) framework to investigate the Chinese learners' adoption behavior of MOOCs. They considered perceived usefulness, performance-to-cost value, interactivity, and accessibility under the technology factors; self regulation, experience, and gender, under the user factors; and learning tradition, peers' impact, instruction and publicity, as the social environmental factors within the TUE framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, they highlighted that perceived usefulness and performance-to-cost value play a significant role in motivating the students to adopt MOOCs. On the other hand, accessibility barriers such as network accessibility and instruction language barrier, refrain learners from adopting MOOCs (Ma & Lee, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations